Serum creatinine/cystatin C ratio is a systemic marker of sarcopenia in patients with gastrointestinal stromal tumours - Ding, Ping’an; Guo, Honghai; Sun, Chenyu; Chen, Shuya; Yang, Peigang; Tian, Yuan; Lowe, Scott; Zhao, Qun (Frontiers in Nutrition, 2022)
Background: It is well known that sarcopenia is a common risk factor in patients with gastrointestinal tumours, which may negatively affect the clinical outcome and prognosis. Recent studies suggest that serum creatinine-cystatin C (Cr/CysC) ratio may be associated with sarcopenia, but this association lacks sufficient evidence in patients with gastrointestinal stromal tumours (GIST). Therefore, this study aimed to investigate whether the Cr/CysC ratio was associated with sarcopenia and recurrence-free survival (RFS) in patients with GIST. Methods: The study retrospectively analysed 413 patients with GIST who underwent surgical resection from January 2016 to January 2020. The serum Cr/CysC ratio was determined as a proxy for sarcopenia by comparing it with various biomarkers and Cox multifactorial analysis was used to determine the relationship between Cr/CysC ratio and prognosis. Results: Serum Cr/CysC was positively correlated with skeletal muscle area (SMA) (r=0.256, p<0.001), skeletal muscle index (SMI) (r=0.300, p<0.001), and hand grip strength (HGS) (r=0.251, p<0.001). The area under the receiver operator characteristic curve for sarcopenic subjects with serum Cr/CysC ratio was significantly greater than other biomarkers (Cr/CysC: 0.840, CysC: 0.732, Cr: 0.518). The optimal cut-off value for Cr/CysC was 0.65, and patients in the high Cr/CysC group had a higher 3-year RFS than those in the low Cr/CysC group (72.46% vs. 92.72%, p<0.001). Cox multifactorial analysis found that the Cr/CysC ratio was an independent risk factor for RFS in GIST patients (HR=2.143, 95% CI: 1.431-5.459, p = 0.011). Conclusion: Serum Cr/CysC ratio has satisfactory and comparable diagnostic accuracy, and prognostic value for sarcopenia in patients with GIST. Therefore, it can be a simple and practical clinical tool to screen sarcopenia in GIST patients. However, further studies are required to validate these findings.